How is research publishing going to progress in the next 20 years? Transcription of Session for Editors, Associate Editors, Publishers and Others with an Interest in Scientific Publishing Held at IADR Meeting In Seattle on Wednesday, 20 March 2013. (May 2014) - Eaton, K. A.; Holland, G. R.; Giannobile, W. V.; Hancocks, S.; Robinson, P. G.; Lynch, C. D.
Abstract On March 20th 2013, a one‐hour session for Editors, Associate Editors, Publishers and others with an interest in scientific publishing was held at the IADR International Session in Seattle. Organised by Kenneth Eaton and Chris Lynch (Chair and Secretary, respectively, of the British Dental Editors Forum), the meeting sought to bring together leading international experts in dental publishing, as well as authors, reviewers and students engaged in research. The meeting was an overwhelming success, with more than 100 attendees. A panel involving four leading dental editors led a discussion on anticipated developments in publishing dental research with much involvement and contribution from audience members. This was the third such meeting held at the IADR for Editors, Associate Editors, Publishers and others with an interest in scientific publishing. A follow up session will take place in Cape Town on 25 June 2014 as part of the annual IADR meeting. The transcript of the meeting is reproduced in this article. Where possible speakers are identified by name. At the first time of mention their role/ position is also stated, thereafter only their name appears. We are grateful to Stephen Hancocks Ltd for their generous sponsorship of this event. For those who were not able to attend the authors hope this article gives a flavour of the discussions and will encourage colleagues to attend future events. Involvement is open to Editors, Associate Editors, Publishers and others with an interest in scientific publishing. It is a very open group and all those with an interest will be welcome to join in.